Intravenous Lormetazepam during Sedation Weaning in a 26-Year-Old Critically Ill Woman - Alawi Luetz; Bjoern Weiss; Claudia D. Spies (Case Reports in Critical Care)
Recent evidence revealed that sedation is related to adverse outcomes including a higher mortality. Despite this fact, patients sometimes require deep sedation for a limited period of time to control, for example, intracranial hypertension. In particular in these cases, weaning from sedation is often challenging due to emerging agitation, stress, and delirium. The submitted research letter reports a rare case of severe and persisting agitation that was unresponsive to all available treatments. Ultimately, lormetazepam which has recently become available for intravenous use in Germany resolved the problem by stress-reduction and anxiolysis without leading to measurable sedation.